Development of an Automated Sign face Cleaner (ASiC) - BIN MUSTAMAM, MUHAMMAD ANIQ FARIS; Al Emran Ismail; Muhd Hafeez Zainulabidin; Mohamad Farid Sies; Mohd Azham Azmi; Mohd Sallehuddin Yusof; Omar Mohd Faizan Marwah; Hanis Zakaria; Maznan Ismon; Mohamad Shah Ikhsan; HASSAN, TS. DR. SUHAIMI BIN HASSAN; Mohd Rasidi Ibrahim (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The prevalence of manual cleaning methods in various industries poses challenges in terms of efficiency, consistency, and labour costs. To overcome these issues, this project proposes the development of an automated surface cleaner that incorporates automation into the cleaning procedure. The goal was to design an automated signboard cleaner controlled by a programmable logic controller and to develop an automation system using a Programmable Logic Controller. The methodology included sensor integration, control systems, and mechanical design concepts. The prototype has some cleaning mechanisms and brushes to efficiently clear surfaces of trash. The prototype’s capacity to follow preset routes and carry out cleaning duties precisely was shown by automation testing results. The creation of this automated surface cleaner, which provides a scalable solution that can be adjusted to diverse situations, has important ramifications for enhancing cleaning procedures in a variety of contexts. Upcoming projects will focus on improving the architecture for energy efficiency and investigating the incorporation of artificial intelligence to improve decision-making skills.